U-Boat 977 - Schaeffer, Heinz (London William Kimber, 1955)
U-boat 977 was the German submarine that escaped to Argentina at the end of World War Two. This epic journey started from Bergen in Norway, where in April 1945 it was temporarily based, and took three and a half months to complete. Because of continuing allied naval activity the commander decided to make the first part of the journey underwater. Before surfacing near the west coast of Africa U-977 had spent a remarkable sixty-six days submerged! It was inevitable that when U-977's journey and escape to Argentina and its port of Mar del Plata became known it would be the center of rumor and theory.
Include Map and Colour Illustration
Foreword by Nicholas Monsarrat
Keywords: World War (1939-1945) -- Military operations, Naval--Submarine -- U 977 (Submarine) -- Military operations, Naval--German -- Schaeffer, H. (Heinz)